How to: manage the room. Designing and facilitating MSP meetings for inclusivity + engagement - Larson, A.M.; Sarmiento Barletti, J.P. (CIFOR-ICRAF, 2023)
Running an inclusive, engaging, and successful MSP is not as simple as inviting everyone around the table (Sarmiento Barletti et al., 2021). The way that you set up and run your meetings – and who you choose to facilitate them (Tamara et al., 2021) – will have major impacts on the breadth and quality of participation, particularly for historically under-represented groups like women, Indigenous Peoples (IPs) and local communities (LCs).